Заощадження домогосподарств: схильність, пріоритети та фактори - Шкварчук, Л. О.; Слав’юк, Р. А.; Сова, О. О.; Shkvarchuk, L.; Slav’yuk, R.; Sova, O. (Видавництво Львівської політехніки, 2020)
Наведено результати дослідження особливостей формування заощаджень домогосподарств в Україні. Порівняно схильність до заощаджень домогосподарств в Україні та країнах Східної Європи за критерієм норми заощаджень. Оцінено пріоритети у формах заощаджень. Обґрунтовано наявність загальної ідентичності заощаджувальної поведінки домогосподарств в Україні та країнах Східної Європи. Визначено основні ознаки домогосподарств, що заощаджують. Інтерпретовано види доходів, які є визначальними для нарощення заощаджень. Виявлено наявність сезонного коливання в обсягах заощаджень та рівнях дохідності депозитів домогосподарств.

This paper investigates the factors behind what determine household saving behavior in Ukraine. The purpose of the article is to evaluate the characteristics of household behavior in Ukraine in terms of savings compared to Eastern European countries. The authors proved that households in Ukraine have a high propensity to save, and their rate of savings in the non-crisis periods is comparable to the values of similar indicators for the most developed countries in Europe. Household savings have been negative during the 2013-2016 crises. Priority form of saving for households is banking deposits. This choice is typical of households in most Eastern European countries. Lowering banks interest rates does not lead to an outflow of household deposits and vice versa. The activity of formation of banks deposits significantly slows down in the middle of the year, which is consistent with the period of seasonal decrease in interest rates of bank deposits. The dynamics of interest rates on deposits is not a determining factor in the decision to open a deposit. The largest amounts of savings are generated by households that receive property income, that is, holders of significant assets, both financially and nonfinancially. There is a direct positive correlation between the amount of savings and the amount of social transfers of households and their mixed income. This shows that the savings are made by the persons receiving the corresponding income: the poorly protected sections of the population and the persons engaged in business activities. The least amount of savings depends on the size and dynamics of wages, that is, employees are least likely to form savings.
Household savings: propensity, priorities and factors
Keywords: заощадження домогосподарств; доходи домогосподарств; схильність до заощаджень; сезонність заощаджень; фактори заощаджень; savings; household income; propensity to save; seasonality of savings; savings factors; D; 19; C; 40; 336.722